2011
DOI: 10.1038/jid.2011.218
|View full text |Cite
|
Sign up to set email alerts
|

Human Cutaneous Melanomas Lacking MITF and Melanocyte Differentiation Antigens Express a Functional Axl Receptor Kinase

Abstract: Axl, a member of the TAM (Tyro3, Axl, Mer) family of receptor tyrosine kinases, displays an increasingly important role in carcinogenesis. Analysis of 58 cutaneous melanoma lines indicated that Axl was expressed in 38% of them, with significant overrepresentation in NRAS- compared with BRAF-mutated tumors. Axl activation could be induced by autocrine production of its ligand, Gas6, in a significant fraction of Axl-positive tumors. Pearson's correlation analysis on expression data from five data sets of melanom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
132
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(157 citation statements)
references
References 38 publications
24
132
0
Order By: Relevance
“…Although PDGFR-␤ was critical for therapeutic escape in this context, the expression of RTKs in melanoma is highly heterogeneous, and could be ultimately patient/tumor-specific. The multiplicity of RTK expression in melanoma cell lines and tumors is suggestive of many potential escape mechanisms and again underscores the need for multiplexed screening platforms such as the one described here (45,46). With regard to the future clinical application of LC-MRM, a situation can be envisaged where the interrogation of adaptive RTK signaling could be used to design personalized, patient-specific MEK/RTK inhibitor combinations that limit the onset of resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Although PDGFR-␤ was critical for therapeutic escape in this context, the expression of RTKs in melanoma is highly heterogeneous, and could be ultimately patient/tumor-specific. The multiplicity of RTK expression in melanoma cell lines and tumors is suggestive of many potential escape mechanisms and again underscores the need for multiplexed screening platforms such as the one described here (45,46). With regard to the future clinical application of LC-MRM, a situation can be envisaged where the interrogation of adaptive RTK signaling could be used to design personalized, patient-specific MEK/RTK inhibitor combinations that limit the onset of resistance.…”
Section: Discussionmentioning
confidence: 99%
“…have previously described melanoma cell expression and secretion of GAS6, the common ligand for all members of the TAM family of proteins, suggesting a method of autocrine and/or paracrine activation of MERTK (18). Since expression of MERTK by melanoma cells increases during progression from primary to metastatic melanoma, it would be interesting to determine whether corresponding increases in GAS6 levels occur in serum from patients with metastatic melanoma, implicating serum GAS6 levels as a potential early marker of melanoma progression, as in other cancers (32).…”
Section: Discussionmentioning
confidence: 99%
“…TYRO3 was identified as an overexpressed receptor in melanoma, a regulator of MITF, and a contributor to the proliferative, antiapoptotic, chemoresistant, and tumorigenic phenotypes of melanoma cells (17). In another study, AXL was commonly expressed in NRAS-mutant melanomas lacking MITF expression and contributed to a migratory and invasive phenotype (18). In addition, Sensi et al found that melanoma cells often secrete GAS6, a ligand of TAM receptors, indicating a mechanism of TAM autocrine signaling in melanoma.…”
Section: Introductionmentioning
confidence: 99%
“…A recent retrospective analysis of patients treated with high dose interleukin (IL)-2 demonstrated that the majority of the responders were NRAS mutant and that patients with either BRAF mutant or BRAF/NRAS wild-type melanoma were less likely to respond (21). Another class of drugs currently undergoing evaluation for multiple cancer types are receptor tyrosine kinase (RTK) inhibitors, and there is evidence that NRAS mutant melanomas may be enriched for expression of RTKs such as c-MET and Axl (22).…”
Section: Future Directionsmentioning
confidence: 99%